1995
DOI: 10.1177/152574019501600206
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Group Training and Individual Feedback on Parent Use of Milieu Teaching

Abstract: disabilities. In a multiple baseline design across families, parents were trained in two conditions: group instruction with home feedback sessions and intensive home feedback sessions. Parents were trained to use seven environmental arrangement strategies and four Milieu Teaching procedures to facilitate their children's acquisition of specific communication targets during eight sessions of group training. The results of the study showed modest levels of performance of the language teaching procedures during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 11 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…Second, despite the advantages of group-based parent education programs, groups alone are not effective (Kaiser et al, 1995); individual support is necessary to support families. In LAPE, the purpose of the individual sessions was to help the parents identify which specific strategies they used well, which new strategies they wanted to start implementing, and how to implement them in their homes.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Second, despite the advantages of group-based parent education programs, groups alone are not effective (Kaiser et al, 1995); individual support is necessary to support families. In LAPE, the purpose of the individual sessions was to help the parents identify which specific strategies they used well, which new strategies they wanted to start implementing, and how to implement them in their homes.…”
Section: Implications For Practicementioning
confidence: 99%
“…Research also supports implementing these approaches with parents during individual and group trainings. Group training, with individualized supports, allows information to be shared in a quick and concise format, provides space and time for shared parent support, and might be less costly (Carter et al, 2011;Kaiser, Hemmeter, Ostrosky, Alpert, & Hancock, 1995). However, the most popular group training programs (e.g., Hanen Centre, 2011) are costly for interventionists, not well suited for current Part C systems, and might not be effective for all families because they are not easily individualized (Carter et al, 2011).…”
Section: Systematic Progress Monitoringmentioning
confidence: 99%
“…This study demonstrated that milieu teaching increased spontaneous speech in three children with ASD providing additional evidence for the use of milieu strategies to teach communication skills to individuals with disabilities (Alpert & Kaiser, 1992;Hemmeter & Kaiser, 1994;Kaiser et al, 1995) and specifically those with ASD (Hancock & Kaiser, 2002;Kaiser et al, 2000;). With careful planning, milieu strategies appear to be a practical means for teachers to provide meaningful instruction to young children with ASD in a variety of typical classroom activities.…”
Section: Discussionmentioning
confidence: 90%
“…Natural communication partners have successfully learned and implemented milieu teaching with children in at-risk families (Peterson, Carta, & Greenwood, 2005) as well as with individuals with disabilities other than ASD (Warren, 1992; Warren & Bambara, 1989; Warren & Gazdag, 1990; Warren, Gazdag, Bambara, & Jones, 1994). Parents have used milieu teaching in both clinic (Alpert & Kaiser, 1992; Hemmeter & Kaiser, 1994; Kaiser, Hemmeter, Ostrosky, Alpert, & Hancock, 1995) and home settings (Alpert & Kaiser, 1992; Kaiser et al, 1995; Peterson et al, 2005). In addition, Hancock and Kaiser (1996) demonstrated that siblings of children with language delays effectively implemented these strategies in ongoing play activities.…”
mentioning
confidence: 99%
“…]; Hallahan & Kauffman, 1997) and class discussion, and encompassed a range of research-validated methods to teach students with a variety of exceptionalities. In addition to generic effective teaching strategies and specific strategies such as CWPT and CBM, strategies presented in the text included using cooperative learning (Johnson & Johnson, 1986) with multicultural and bilingual students; applied behavior analysis (Wolery, Bailey, & Sugai, 1988) and task analysis (Moyers & Dardig, 1978) for students with mental retardation; scaffolded instruction (Palincsar, 1986) (Kaiser, Hemmeter, Ostrosky, Alpert, & Hancock, 1995) with students who have language disabilities or delays; total communication with students who are deaf; and multiple intelligences (Gardner & Hatch, 1989) and ability grouping with students who are gifted (VanTasselBaska, 1992).…”
Section: Effective Instructional Strategies Formentioning
confidence: 99%